The Impact of Early Weight-Bearing on Functional Recovery After Primary Total Ankle Arthroplasty - Matthew T. Nguyen MD; Brian M. Weatherford MD; Melissa M. Gross MD; Brett Drake BSc(Med); Apurva Choubey MD (Foot & Ankle Orthopaedics)
Category: Ankle Arthritis; Ankle Introduction/Purpose: Total ankle arthroplasty (TAA) has become a viable option for the treatment of end-stage ankle arthritis. Initiation of weightbearing after a TAA has traditionally been conservative with anywhere from 6 to 12 weeks of non-weight bearing recommended by surgeons. To date, there has been a paucity of literature examining the impact of early weightbearing after TAA on postoperative outcomes. The objective of this study was to compare weightbearing at 3 weeks versus 6 weeks on functional recovery after primary TAA. We hypothesized that patients allowed to weight bear at 3 weeks would exhibit greater improvements in range of motion (ROM) without any increase in postoperative complications. Methods: In this retrospective cohort study, we analyzed patients who underwent a primary TAA by a single surgeon from January 2018 to March 2023 using the INBONE 2 prosthesis. These patients were separated into 2 groups – those who began initiation of weightbearing at 3 (n=50) weeks and those at 6 (n=27) weeks. Basic demographic data and postoperative complications was collected for both groups. Ankle ROM was collected and measured from both pre- and postoperative ankle dorsi-flexion and plantar-flexion radiographs at routine postoperative visits. Postoperative complications were additionally subcategorized into major or minor. Comparisons between groups were performed with Student T-test for independent variables, paired T-test for in-group comparisons, and Chi-square test for categorical variables with P < 0.05 considered to be statistically significant. Kaplan-Meier survival plots were created for overall, minor, and major complication rates. Results: Sex, smoking status, diabetes, obesity, and arthritis etiology did not statistically differ between groups. The 3-week weightbearing group was significantly older than the 6-week group (67.8 years vs 61.1 years, respectively, P=0.013). Patients in the 3-week group had statistically greater improvements in their postoperative ankle ROM at 6 weeks, 6 months, 1 year, and 2 years compared to their preoperative ankle ROM. Furthermore, patients in the 3-week group had statistically greater increases in postoperative ankle ROM at 6 weeks, 6 months, and 1 year compared to their 6-week counterparts. Total number of overall, minor, or major complications did not differ significantly between groups. The time to first overall, minor, or major complication also did not differ significantly between groups. Conclusion: The initiation of early weightbearing at 3 weeks postoperative after a primary TAA appears to bring about greater improvements in postoperative ankle ROM compared to preoperative ROM that is sustained even out to 2 years postoperative. Furthermore, the early weightbearing group demonstrated increased ankle ROM compared to the delayed weightbearing group at medium-term follow-up without any increase in complications. These findings suggest earlier initiation of weightbearing after a primary TAA is safe and even beneficial in terms of motion.